Research on distribution characteristic of “three zones” of coal spontaneous combustion in goaf with double cut roof retaining roadway - Lijuan JIANG; Junhu ZHANG; Cunbao DENG; Jun NIAN; Meng CAI; Xiaobo LYU; Changkui LEI (Meikuang Anquan, 2023)
In order to study the distribution characteristics of the “three zones” of coal spontaneous combustion in the goaf of double cut roof retained roadway, taking the working face 4502 of Shaqu No.1 Mine as the engineering background, a combination of on-site monitoring and numerical simulation was adopted to study the air leakage law and the distribution characteristics of the “three zones” of coal spontaneous combustion in the goaf of the working face 4502 with double cut roof retained roadway. The results show that the main air leakage areas in the goaf of the double cut roof retaining roadway are the corners of the working face and the retaining roadways on both sides. The air flow mainly leaks into the goaf from the corners on both sides, and there is air exchange between the goaf and the retaining roadways on both sides. There is a slender oxidation zone on the side of the double retaining roadway, and the oxidation zone is distributed in a U-shaped throughout the goaf. At different stages of mining, there are significant differences in the distribution of the “three zones” of coal spontaneous combustion in the working face with double cut roof retaining roadway. In the initial stage of mining, it is necessary to strengthen the prevention and control of coal spontaneous combustion within a range of 5 m on the side of the double cut roof retaining roadway and 32-65 m in the middle of the goaf. In the middle and later stages of mining, it is necessary to strengthen the prevention and control of coal spontaneous combustion within a range of 2.5 m on the side of the transportation retaining roadway, within a range of 12 m after 38 m from the track retaining roadway, and within a range of 30-80 m in the middle of the goaf.